2015
DOI: 10.1088/0143-0807/36/5/055020
|View full text |Cite
|
Sign up to set email alerts
|

A simple demonstration of Einstein's lift: a body thrown upwards moves rectilinearly and uniformly relative to a free-falling model of the lift

Abstract: The educational model of Einsteinʼs lift consists of a table suspended from an electromagnet. A flexible support is attached to the table. A metal ball is on the support and deforms it. When the electromagnet is deenergized, the table falls, the system goes to a weightless state and the support throws the ball up. A camera carries out frame-by-frame photography of the free-falling model. The resulting photographs are imported into a computer, projected on to a screen with a multimedia projector and analyzed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
(8 reference statements)
0
9
0
Order By: Relevance
“…In the background of Galilean relativity student difficulties with inertial frames of reference have been documented [3][4][5] and considering different frames of references in a given problem sometimes is difficult for students [6]. Researchers have observed that these topics can be more effectively understood if students perform experiments, carry out data acquisitions and quantitative analysis, and actually see a phenomenon in different frames of reference [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the background of Galilean relativity student difficulties with inertial frames of reference have been documented [3][4][5] and considering different frames of references in a given problem sometimes is difficult for students [6]. Researchers have observed that these topics can be more effectively understood if students perform experiments, carry out data acquisitions and quantitative analysis, and actually see a phenomenon in different frames of reference [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent paper [7] the authors presented an educational model of Einstein's lift. In that model of lift, an elastic sheet was deformed by a small sphere when the lift is at rest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Student difficulties with inertial reference frames and relative motion have been documented in some papers in the past [1][2] while more recently students' understanding of the PoE and RP was also investigated [4][5]. According to some authors, learning effectiveness can be improved when students are allowed to see a movement in different frames of reference and perform the experiments independently while carrying out quantitative estimates.…”
mentioning
confidence: 99%
“…Although there are some "good" educational experiments, few are available for inexpert students while most require that students and teachers have advanced experimental skills. Many experiments were focused on demonstration of Einstein's lift [5,6] and on the physics of free fall, as the ones illustrated in ref [7] where the author reported a collection of experiments by employing techniques that can be implemented by unskilled students. These experiments integrate new technologies such as smartphones and free software (Tracker®) for video analysis.…”
mentioning
confidence: 99%